化简(2a-3b)(3a-2b)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 08:05:57
化简(2a-3b)(3a-2b)化简(2a-3b)(3a-2b)化简(2a-3b)(3a-2b)(2a-3b)(3a-2b)=6a²-4ab-9ab+6b²=6a²-13
化简(2a-3b)(3a-2b)
化简(2a-3b)(3a-2b)
化简(2a-3b)(3a-2b)
(2a-3b)(3a-2b)
=6a²-4ab-9ab+6b²
=6a²-13ab+6b²
6a^2-13ab+6b^2
6a²-13ab+6b²
化简a-(3a-b)+(2a+3b)
化简(2a-b/a+b-b/a-b)÷a-2a/a-b
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
a-{b-2a+[3a-2(b+2a)+5b]}化简
化简a/b(a-b)-b/a(a-b)其中a=3 b=-2
(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程
[3(a+b)^4-1/2(a+b)-a-b]/(a+b)
2(a-b)²(a+b)-(b-a)²(3a-b)因式分解
2b²+(a+b)(a-b)-(a-b)²,其中a=-3
计算(a/a-b+b/b-a)/(1/a+b)的结果 (1)a-b (2)ab (3)a^2-b^2 (4)a+b
化简(-0.5a+3b)(a-2b)
(4a-b)-2(a-3b)化简
3(a+5b)-2(b-a) 化简
A=B+B+B+B+B+B+B+B+B+B+B+B+B+B+B A-B×3=C C+2×7+2=1A=B+B+B+B+B+B+B+B+B+B+B+B+B+B+BA-B×3=CC+2×7+2=148148-(C-32)=DA,B,C,D各是多少?
3(a+b)^2-(a+b)+2(a+b)^2-(a+b)^3+4(a+b)合并同类项
计算:2/3A-2/A+B{A+B/3A-(A+B)}等于多少?
5(a-b)^-3(a-b)^2-7(a-b)-(a-b)^2+7(a-b)合并同类项
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)